Reconsidering Inclusion: Western theory and post-Soviet reality - Hallett, Fiona; Allan, David; Hallett, Graham (Disability Studies Quarterly, 2019)
This article analyses the views of individuals from a post-Soviet context in order to better understand current thinking around difference and disability. In this study, the multiplicity of human experience articulated by the research participants highlights immediate, rather than philosophical, priorities. The particular social, cultural and political history of the Republic of Armenia offers an insight into the challenges of, and opportunities for, the development of inclusive practices in the former Soviet Union. As such, it could be argued that the West has much to learn from national contexts that might be dismissed as exclusionary.